Mangrove Care Social Action for Conservation and Development Ecotourism in East Kutai - Eny Heriyati; Anshar Haryasakti (Universitas Muhammadiyah Palembang, 2024)
The social activities of STIPER East Kutai Marine Science lecturers as a form of Community Service activity is carrying out mangrove conservation activities in the Teluk Lingga area. Conservation is a method and effort to utilize available resources to ensure their sustainability in the future. Community service in the form of planting 6000 mangrove seedlings aims to conserve the Lingga Bay mangrove forest and ecotourism in the East Kutai coastal area. The smooth implementation of this Community Service was thanks to the collaboration of all levels of the East Kutai community with the Ministry of Forestry, the Watershed Forum, the Coastal Area Observer Forum and regional leadership in East Kutai. The type of mangrove planted is Avicennia sp. Apart from being carried out by lecturers, this 6000 mangrove planting event was also attended by students, East Kutai High School and Vocational School students and the general public in the Teluk Lingga area. The success of mangrove conservation activities can make the Lingga Bay coastal area an ecotourism area for the East Kutai Community.